Study on Fermentation Process of Lactic Acid Bacteria Inoculated with Kimchi. (October 2019) - Sui, Ming; Zhang, Yang; Rong, Jiachao; Zhu, Keyong; Wei, Mingying
Abstract: This paper uses cabbage as raw material to ferment kimchi through lactic acid bacteria inoculation. Using sensory score, total acid, pH and nitrite content as indicators, the main factors affecting the fermentation of lactic acid bacteria inoculated kimchi were investigated. The optimum technological conditions for inoculating fermentation of Kimchi lactic acid bacteria were determined by experiments. The lactic acid bacteria grow rapidly during the fermentation process and produce lactic acid, which lowers the pH value of the kimchi. The protein in the kimchi is decomposed into free amino acids, and the calcium ions are combined into inorganic salts, which have high nutritional value.